How Life Cycle Assessment Supports Sustainability Reporting: Example from Clean Aviation - Ana Claudia Nioac de Salles; Peter Brantsch (Engineering Proceedings, 2025)
The aim of this work is to present how the Life Cycle Assessment (LCA) tool can support sustainability reporting. A comprehensive analysis enables organizations to generate precise and quantitative data, e.g., on resource consumption, thus aligning with sustainability goals outlined in the reports. By pinpointing these areas, organizations can prioritize efforts to improve environmental performance where it matters most, ensuring that sustainability initiatives are focused and effective. Overall, the LCA serves as a valuable tool for organizations seeking to comply with sustainability reporting by providing robust data, insights, and guidance for improving environmental performance and fostering sustainable practices.